Healing and reconciliation as a pastoral ministry in post-conflict South African Christian communities - Manda, Charles B. (Verbum et ecclesia, 2017)
Although Jeremiah's lamentation is directed towards the wound of God's people in Zion, Africa remains the site of struggle for political, socio-economic and religious freedoms. Is there no balm in Africa to heal the wound of God's people? This article examined the principles of healing and reconciliation as understood in the South African cosmology and how or whether they could be applied by the pastoral ministry to enhance the recovery and restoration of African Christian communities in post-conflict situations. To get the relevant data, the authors engaged literature written on these concepts of healing and reconciliation and how they are applied in a broader context. The authors also used their experiences in the field of healing to illustrate some points.Intradisciplinary and/or interdisciplinary implications: Although the article is focussed on the role of the pastoral ministry within the South African cosmology, this study has interdisciplinary implications in the disciplines of peacebuilding, mental health and psychosocial support. The author argues that when these social and cultural aspects of healing and reconciliation are taken into consideration, they could enhance post-conflict reconstruction and social transformation of post-conflict African communities.